Assessment Instruments for Tarkib and Mufrodat in the Ministry of Religion's Arabic Language Textbook - An Nury, Ahmad Husein; Hikmah, Hikmah; Masrun, Masrun (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
This research aims to analyze the evaluation instruments for sentence structure (tarkib) and vocabulary (mufrodat) in the Arabic language textbook for ninth grade published by the Ministry of Religious Affairs, section al-Haflu bi maulidi ar-Rasul ﷺ. The approach used is qualitative descriptive and content analysis to assess the alignment of the questions with the theory formulated by Muhammad A’li Al-Khuli in his book Al-Ikhtibaarot Al-Lughowiyyah. This research uses the Miles and Huberman data analysis model, which includes data collection, reduction, presentation, and verification to obtain valid and systematic findings. The research results reveal that the details of the analyzed questions can be classified into categories of question items as outlined in the book Al-Ikhtibaarot Al-Lughowiyyah, showing a combination of various types of question items. Out of a total of 51 items, there are 31 items of composition and vocabulary according to the evaluation categories formulated by Muhammad A’li Al-Khuli in Al-Ikhtibaarot Al-Lughowiyyah, 26 composition items and 5 vocabulary items, while the rest do not conform to the evaluation categories according to Muhammad A’li Al-Khuli in his book. This study emphasizes the importance of developing evaluation instruments that are in accordance with linguistic theory to be effective in measuring the achievement of student competencies in learning Arabic.